Investigation on Electrical Properties and Microdefects of Nb5+-Doped BaTiO3 Based Ceramics by Positron Annihilation Techniques - Xuxin Cheng; Yuxin Wang; Xiaoming Chen; Haining Cui (Materials Research, 2019)
The influence of the Nb5+-doped content and the doping CaCO3 on the electrical properties and the microdefects of BSTN ceramics by Positron Annihilation Techniques were studied, which were fired at 1350 ºC for 2 hours in air. The PTCR characteristics in the BSTN samples were also investigated. Moreover, the information on microdefects in BSTN ceramics was demonstrated by coincidence Doppler broadening spectrum measurements and positron annihilation lifetime spectra. Meanwhile, the influence of the defects on the electrical properties of the ceramics was also revealed. Furthermore, the critical donor-dopant content was 0.4 mol%, which corresponding room-temperature resistivity and the resistivity jumping ratio was 714.3 Ω·cm and 2.77 × 102, respectively. In addition, the average positrons annihilate lifetime t of the BSTN ceramics was investigated as well.